Aktivitas antihelmintik areca catechu sebagai kandidat obat tradisional: literature review - Putri, Rizkina Amanda (Maliki Interdisciplinary Journal, 2025)
oncern in Indonesia, and resistance to synthetic drugs such as albendazole and levamisole highlights the need for natural alternatives. Areca catechu L. (betel nut) has long been used in traditional medicine to treat helminthiasis. This article presents a literature review of 10 journals published between 2015 and 2025, retrieved from Google Scholar using the keywords “Areca catechu”, “betel nut”, “anthelmintic”, and “traditional medicine”. A qualitative analysis was performed covering extract type, dosage, research methods, parameters, and outcomes. The review found that A. catechu extracts, including aqueous infusions, ethanol extracts, and organic fractions, exhibit ovicidal, larvicidal, and vermicidal activity against Ascaridia galli, Haemonchus contortus, and Fasciola spp., with moderate to high concentrations often showing effectiveness comparable to synthetic drugs. A consistent dose-response pattern was observed, although data on toxicity and standardized dosing remain limited. Therefore, A. catechu holds strong potential as a traditional anthelmintic candidate, yet further research is required to ensure its safety and clinical applicability.